Integration of Project-Based Learning and Deep Learning Approaches in Elementary School Science Learning in the Independent Curriculum - Ega Krisna Pradita; Endang Widi Winarni; Rendy Wikrama Wardana; Abdul Muktadir (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study aims to describe the implementation of Project Based Learning (PjBL) based on a deep learning approach in elementary school science learning under the Independent Curriculum. The study used a descriptive qualitative approach with a field research type at Tepungsari Public Elementary School. The research subjects consisted of a fifth-grade teacher and 27 students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and data verification. The results showed that the implementation of PjBL was able to create active, contextual, and meaningful science learning through project activities based on the surrounding environment. The deep learning approach encouraged students to think critically, creatively, collaboratively, and reflectively during the learning process. Student creativity was seen through the ability to generate ideas, modify projects, and communicate results communicatively. Implementation constraints included limited time, learning facilities, and differences in student abilities. Teachers overcame these constraints through group mentoring, staged project management, and the use of simple media. This study provides implications that deep learning-based PjBL can be an innovative learning alternative in enhancing elementary school students' creativity under the Independent Curriculum.